Influence factors for upper respiratory tract infection in Chinese rural children: A cross-sectional study - Wu, Bichen; Luo, Shujuan; Xu, Chang; Yang, Ting; Chen, Yanping (Frontiers in Pediatrics, 2022)
Aim: The prevalence rate of upper respiratory tract infection (URTI) is high in children. Influencing factors for URTI have been reported in Chinese urban children, but those have not been explored in rural children. In China, children in the rural area are a disadvantaged group. Therefore, this study aims to explore influencing factors for URTI in Chinese rural children. Methods: This was a cross-sectional study based on the 1991-2015 China Health and Nutrition Survey (CHNS). In total, 5,289 children were eligible for our analysis, with 3,684 rural children and 1,605 urban children. The generalized estimating equation was used to determine the influencing factors, and results were expressed as odds ratios (ORs) with 95% confidence intervals (95% CIs). Results: Our results showed that rural children aged 7-12 years and 13-17 years had lower odds of URTI than those aged 0-1 year, with OR value of 0.17 (95%CI: 0.11-0.27) and 0.12 (95%CI: 0.08-0.19), respectively. Compared to uneducated mothers, mothers with education level of primary school (OR: 0.59, 95%CI: 0.42-0.84), lower middle school (OR: 0.53, 95%CI: 0.38-0.73), and upper middle school and technical school (OR: 0.62, 95%CI: 0.40-0.95) was associated with the lower odds of URTI in rural children. Children, whose mother was office worker, had 46% lower odds of URTI than those with farmer mother (OR: 0.54, 95%CI: 0.34-0.84). Conclusions: Our study found mother’s education level, children’s age, and mother’s occupation were significant influencing factors for URTI, which suggested the importance to improve mother’s health-related knowledge and working conditions in Chinese rural area.